Implementation of an adapted Sepsis Risk Calculator algorithm to reduce antibiotic usage in the management of early onset neonatal sepsis: a multicentre initiative in Wales, UK. Issue 3 (22nd September 2021) - Goel, Nitin; Cannell, Stephanie; Davies, Gemma; Natti, Murali Sridhar; Kirupaalar, Vickness; Abelian, Artur; Saeed, Shakir; Smith, Rhian; Manikonda, Ravi; Pitchaikani, Prem Kumar; Davies, Dawn; Morris, Rachel May; et al.
Abstract : Objective: Assess the impact of introducing a consensus guideline incorporating an adapted Sepsis Risk Calculator (SRC) algorithm, in the management of early onset neonatal sepsis (EONS), on antibiotic usage and patient safety. Design: Multicentre prospective study Setting: Ten perinatal hospitals in Wales, UK. Patients: All live births ≥34 weeks' gestation over a 12-month period (April 2019–March 2020) compared with infants in the preceding 15-month period (January 2018–March 2019) as a baseline. Methods: The consensus guideline was introduced in clinical practice on 1 April 2019. It incorporated a modified SRC algorithm, enhanced in-hospital surveillance, ongoing quality assurance, standardised staff training and parent education. The main outcome measure was antibiotic usage/1000 live births, balancing this with analysis of harm from delayed diagnosis and treatment, disease severity and readmissions from true sepsis. Outcome measures were analysed using statistical process control charts. Main outcome measures: Proportion of antibiotic use in infants ≥34 weeks' gestation. Results: 4304 (14.3%) of the 30 105 live-born infants received antibiotics in the baseline period compared with 1917 (7.7%) of 24 749 infants in the intervention period (45.5% mean reduction). All 19 infants with culture-positive sepsis in the postimplementation phase were identified and treated appropriately. There were no increases in sepsis-related neonatal unit admissions, disease morbidity and late readmissions. Conclusions: This multicentre study provides evidence that a judicious adaptation of the SRC incorporating enhanced surveillance can be safely introduced in the National Health Service and is effective in reducing antibiotic use for EONS without increasing morbidity and mortality. Abstract : Antibiotic use in the newborn may have long lasting impact. Neonatal sepsis is relatively rare but one which causes concern, investigation and treatment. This paper describes the implementation of an sepsis risk calculator to reduce antibiotic use in a safe and sustainable way.